Effect of different levels of dietary calcium on performance and mineral availability in crossbred dairy cattle - Smitha Wilson (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 2006)
An investigation spread over a period of four months was undertaken in crossbred dairy cattle to assess the effect of different levels of dietary calcium on the performance and mineral availability in cross bred dairy cattle. Twelve healthy crossbred cows in the last month of pregnancy having an average peak yield of minimum eight litres per day in their previous lactation were selected. They were divided into two groups of six each as uniformly as possible with regard to age and milk yield and allotted to two dietary treatments viz., T1 (control ration) where in the compounded cattle feed contained 0.5 per cent calcium as per IS (1992) standards and T2 (experimental ration) where in compounded cattle feed contained 1.0 per cent calcium. Paddy straw was the sole roughage source in both the rations. All the experimental animals were fed as per ICAR (1999) standards except for dietary Ca and maintained individually on their respective dietary regime from the last month of calving to three months of lactation. Average dry matter intake, fortnightly body weight, milk yield, milk fat percentage, total solids, solids not fat, serum minerals, mineral content of milk, balance of Ca, P, Mg and Zn and incidence of metabolic disorders were the criteria employed for evaluation. Average body weights and dry matter intake of animals revealed no significant difference for both the groups during all the fortnights studied. Highest dry matter intake for the group I was recorded during the third fortnight and for group II in the second and third fortnight. Average daily milk yield, fat percent, total solids and solids not fat per cent in milk in all the six fortnights did not differ significantly between the groups. The average mineral concentration in milk collected after calving, and at the first, second and third month of lactation for the animals in group II and I did not differ significantly. The mineral content in serum and milk in both groups were within the normal range reported for the species. Results with respect to balance of P and Zn did not differ significantly whereas that for Ca, and Mg differed significantly (P<0.05) between the two groups. Higher retention values were recorded in group II for Ca and group I for Mg. The average retention percent of Ca and Mg differed significantly (P<0.05) the higher values recorded in group I for Mg and in group II for Ca. There was no incidence of metabolic disorders like hypocalcaemia, hypomagnesaemia and ketosis in both groups of animals. An overall critical evaluation of the results obtained in the present study helps to infer that different levels of calcium followed in the present study has a major effect on improving the Ca balance of early lactating cows. The results suggest that levels of Ca in compounded cattle feed at one per cent is better than 0.5 per cent to avoid negative balance of calcium during early lactation when paddy straw is the sole roughage source. The study also indicates that with high levels of dietary Ca there is a need for Mg supplementation to avoid negative balance arising due to interaction of the two elements.